PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA CV RATNA BALI - Putra, Ida Bagus Yogi Pratama; Kusuma, I Gede Budi Adi (Jurnal MBE Manajemen Bisnis, Equilibrium, 2024)
Factors that influence employee performance are transformational leadership, work discipline, and compensation. Ratna Bali with a sample of 35 respondents in this study. The data in this research was collected through questionnaires, processed and analyzed using the data analysis techniques used in this research, namely Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, F Test and t Test. Based on the results of research analysis, Transformational Leadership style has a positive and insignificant effect on employee performance at CV. Ratna Bali. Work discipline has a positive and significant effect on employee performance at CV. Ratna Bali. Compensation has a positive and significant effect on employee performance at CV. Ratna Bali. Simultaneously, transformational leadership, work discipline and compensation have a positive and significant effect on employee performance at CV. Ratna Bali. Suggestions for researchers for further research include the need for further research into other factors that also influence employee performance.